PENGEMBANGAN KEMAMPUAN BERPIKIR MATEMATIK DENGAN METODE MOORE TERMODIFIKASI - Muhammad Huda Firdaus; Winmery Lasma Habeahan; Arie Candra Panjaitan (Universitas Islam Sumatera Utara, 2022)
The ability to think mathematically is an ability that every student and teacher of mathematics needs to be able to understand mathematics better. Various studies have been conducted to apply appropriate approaches and learning methods to develop this mathematical thinking ability. This paper is a theoretical study, which will briefly describe one alternative learning method, which is expected to develop this ability. The alternative method that will be described is the Modified Moore method, which provides opportunities for students to be actively involved in learning, with little direction or guidance from the teacher.